Comparing Spiritual Narratives of Ibn Jubayr and Nizami - Muhammad Ihwan Safrudin; Muhammad Haidar Gibran; Aria Raizal Muhammad; Nurholis (Journal of Literature Review, 2025)
This comparative study analyzes the narrative and spiritual themes in two foundational works of Islamic literary tradition: A Pilgrimage to Mecca (a rihla or travelogue) by the 12th-century Andalusian scholar Ibn Jubayr, and Star-Crossed Lovers or Layla and Majnun (a masnavi or epic poem) by the Persian poet Nizami Ganjavi. Despite originating from different genres, languages, and purposes, one being a factual travel account and the other being an allegorical romance. Both masterpieces convergently explore the transformative journey of the human soul. Ibn Jubayr's work presents the physical Hajj as a profound spiritual pilgrimage. Through meticulous empirical observation of sacred sites and Muslim communities, his narrative transcends mere reportage to become a reflection on divine order, personal piety, and the unity of the Ummah. Conversely, Nizami's tragic tale of the "Star-Crossed Lovers" uses the framework of unrequited worldly love as a powerful Sufi metaphor. Majnun's madness and his longing for Layla symbolize the soul's total and self-annihilating (fana) quest for union with the Divine. By analyzing the narrative structures, thematic parallels, stylistic devices, and socio-historical contexts of both texts drawing upon analyses by Netton (1996) and Chelkowski (1975). This research aims to demonstrate how the journey narrative, whether literal or metaphorical, functions as a primary vehicle for spiritual articulation. Ultimately, this comparison highlights the diversity and depth of spiritual expression in the classical Islamic world, where the path to God could be mapped through both a real journey in the world and through the inner landscape of the human heart.